Activation of Blood Coagulation after Abrupt or Stepwise Withdrawal of Oral Anticoagulants - A Prospective Study - Palareti, G; Legnani, C; Guazzaloca, G; Frascaro, M; Grauso, F; De Rosa, F; Fortunato, G; Coccheri, S (Thrombosis and Haemostasis, 1994)
The occurrence of a “rebound hypercoagulable state” in patients after discontinuation of oral anticoagulants is still a matter of debate and no definite recommendation can be made on the best procedure for anticoagulant withdrawal. The present study investigated the changes in the levels of markers of activated blood coagulation in 32 patients (pts) in whom warfarin treatment (for venous thromboembolic disease) was randomly withdrawn abruptly (n = 17, group A) or gradually (n = 15, group B: ⅔ of initial dose the 1st week, ⅓ the 2nd weeks and nothing from the 3rd week on). Blood was sampled at baseline, once a week for the first three weeks and after 2 months. At the 1st week group A had significantly higher F1+2 and TAT values (p <0.001); at the 2nd week F1 + 2 levels remained higher (p <0.05) though INR values were not different from those of group B. After baseline, higher than normal F1+2 levels were recorded in 32/66 (48%) controls in group A vs 15/60 (25%) in group B (p <0.01); at the 2nd week, 10/17 (59%) patients in group A vs 1/15 (7%) in group B still had higher than normal F1+2 levels (p <0.01 ). The values of areas under curve (AUC) and maximum concentrations of all variables were not statistically different in the two groups; however, very high levels were observed in a few cases of group A. Thrombotic events (one DVT recurrence and one thrombophlebitis in a varicose vein) occurred in 2 pts of group A, both with high F1+2 and TAT AUC values. In conclusion, the present study shows that withdrawal of oral anticoagulants elicits low grade transient clotting activation, which is more intense and longer lasting after abrupt discontinuation. In single cases, however, such activation is particularly intense. It is possible that these cases are at greater risk of thrombotic complications.